INTEGRATED OF GEOMECHANICS WELLBORE STABILITY & SWEET SPOT ZONE ANALYSIS TO UNCONVENTIONAL WELL DRILLING OPTIMIZATION - Allen Haryanto Lukmana (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2020)
Abstract Central Sumatra Basin is one of the largest hydrocarbon producer basins in Indonesia. The largest hydrocarbons accumulation in this basin does not rule out the possibility of hydrocarbons also trapped in shale source rock. The potential for hydrocarbon shale is in the Brown Shale Pematang Group layer. The obstacle to development is the depth of the Brown Shale layer so deep that further case studies are needed. This study aims to analyze the geomechanical wellbore stability modelling for drilling and determination sweet spot zone supported by x-ray diffraction (XRD), brittleness index (BI), total organic carbon (TOC) analysis. The geomechanical wellbore stability modelling based on pore pressure, shear failure gradient/collapse pressure, fracture gradient, normal compaction trend, minimum horizontal stress, maximum horizontal stress and overburden gradient analysis. Brittleness index considers each parameter from XRD data which dominantly contains clay, quartz, and calcium. Based on XRD analysis of shale samples from Limapuluh Koto Area, it showed that the samples included the brittle shale group because of the dominant quartz, while the samples from Kiliran Jao were shale brittle because of dominant carbonate (carbonate-rich). From laboratory test results of 8 rock samples from Brown Shale Formation outcrop in Limapuluh Koto Area, it was obtained total organic carbon (TOC) value is 4-17% (average 8%). The shale thickness estimated > 30 m, the brittleness index shale estimated 0.71, and the gradient of over-pressure on Brown Sahle Pematang Group estimated 0.57 psi/ft & 0.53 psi/ft from log data analysis. So the output of this results the study is expected to get stable borehole, minimum of non-productive time (NPT), the problem when drilling such as caving and sloughing. Based on (Mt, 2013), the prospect criteria results can be concluded that the Brown Shale Formation has good unconventional hydrocarbon shale potential. It can be carried out with further research.